Teaching as a practice - Mafeka, Mahali (My University, 2014)
The aim of this conceptual investigation is to reclaim the ethics of teaching through a critical examination of some recent accounts of good practice in teaching and by advancing an alternative account. Many recent accounts of good practice focus on concepts such as professionalism, competence and reflective practice. In some of these accounts, the ethical dimension of teaching is central and explicit; in others, it is only implicit; in yet others, it is distorted or even ignored. This inattention to ethics in theoretical accounts is paralleled in practice by teachers' failure to understand teaching as a moral enterprise, as is exemplified by responses of teachers to some of the teaching problems that they encounter. This research gives an alternative account of teaching as a practice through using Alasdair MacIntyre's conception of a practice. Key term in MacIntyre's conception are internal and external goods, standards of excellence and virtue. It is shown that the acquisition of the goods internal rather than the goods external to teaching is necessary but not sufficient for a flourishing practice of teaching. The conception of teaching as a practice is also used in this investigation to reflect on the roles of teachers as specified by the new Norms and Standards Teacher Education in South Africa. If well understood, the roles of teachers are not made up of mere lists of tasks and competences. The notion of teachers' roles opens the way for reclaiming an ethics of teaching.
Keywords: Teaching--methodology